The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3221/igf-esis.59.25
|View full text |Cite
|
Sign up to set email alerts
|

Reinforced Soft Soil by CSV with/without Polypropylene fibres: Experimental and Numerical analysis.

Abstract: Columns of mixed soil-sand-cement (CSV), is one of the most unknown used methods for soft soil stabilization that has not been studied before. To this end, in this paper, consolidated drained (CD) triaxial compression tests after have been cured for 28 days, were carried out to investigate the effectiveness of CSV, which is mainly used to reinforce soft soil. Then, the influence of soft soil content (25%, 50%, 75%) on materials of CSV with/without polypropylene (PP) fibers is established. The percentages of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…7 and Figs. (13)(14)(15)(16) show the results of the numerical modelling. The safety factor increases as cement content and fibre lengthens.…”
Section: Results Of the Numerical Modelling And Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 and Figs. (13)(14)(15)(16) show the results of the numerical modelling. The safety factor increases as cement content and fibre lengthens.…”
Section: Results Of the Numerical Modelling And Discussionmentioning
confidence: 99%
“…When the volume variation reaches constant values, the consolidation is complete. 6-Under draining circumstances with an axial displacement rate of 1 mm/min, shear loading is given with regard to a constant confining pressure to specimen failure [11][12][13].…”
Section: Triaxial Test Proceduresmentioning
confidence: 99%
“…Gray and Ohashi (GRAY and OHASHI, 1983) showed that the incoporate of fibre to the soil tested improved the soil's shear resistance and compression significantly. In recent years, this area has seen significant advances in civil engineering practice and geotechnical engineering in particular; for example, (SOUADEUK and BOUDAOUD, 2021) studied the effect of mixed soil-sandcement columns with or without polypropylene (PP) fibres, the experimental results of consolidated drained (CD) proved that the fibres mixed with the soft soil are effective in improving the mechanical properties of the studied soil. (YASMINE and ZEINEDDINE, 2022) They indicated that 1% of polypropylene fibres (12mm and 18mm) mixed with cement content (0, 3, and 6%) and sand through the consolidated drained triaxial test increased both the cohesion and friction angle of sands.…”
Section: Introductionmentioning
confidence: 99%